Clinicopathological Evaluation of Breast Lump in Different Age Groups - Hassan, Mohammad Mahmudul; Ahamad, Farid Uddin; Khan, Mohammad Ashraf Uddin; Fatema, Most Bilkis; Kamal, Mohammad Mustafa; Azam, ANM Nure; Tani, Sadia Afrin (Journal of Dhaka Medical College, 2023)
Background: Breast masses have a variety of etiologies, benign and malignant. Fibroadenoma is the most common benign breast mass; invasive ductal carcinoma is the most common malignancy. Most masses are benign, but breast cancer is the most common cancer and the leading cause of cancer deaths in women. Although most breast cancers occur in women older than 50, a significant number of women are diagnosed with breast cancer younger than 50. An efficient and accurate evaluation can maximize cancer detection and minimize unnecessary testing and procedures. Objectives: Our study aimed to explore the frequency & pattern of different types of breast lumps in various age groups. Materials & method: This cross-sectional observational study was carried out in the inpatient and outpatient department of surgery at Shaheed Ziaur Rahman Medical College Hospital, Bogra, from July 2008 to Dec 2008. A total of 130 patients with palpable breast lumps were included in the study. The age of the patients was between 11 to 70 years. Fine Needle Aspiration Cytology and biopsy were done for most of the patients with a breast lump. Sometimes ultrasonography, mammography, and other routine investigations were also done. Result: In this study, the most common age was 11 to 20. The three most common diseases presented with lumps were Fibroadenoma, Carcinoma of the breast, and fibroadenosis. Peak age incidence of fibroadenoma was observed in the 11 to 20 age group (66%), while fibroadenosis was common in the third decade (46%), and peak age incidence was between the late twenties and early thirties. Carcinoma of the breast was common in 31 to 40 years age group (40%). No carcinoma was found below the age of 22 years. Most of the patients with carcinoma presented in an advanced stage. This reflects on illiteracy, poverty, lack of awareness, and medical facilities screening procedure in our population. Conclusion: The diversity of clinical presentation of breast lumps in different age groups was observed in our hospital practice, and a correlation between clinical manifestations, FNAC findings, and histological diagnosis of breast lumps was made. Fibroadenoma was common in the second and third decades, while breast carcinoma was common in third and fourth decades. Here we attempted to find out the age incidence of the breast lump and its correlation with clinical features, FNAC findings, and histopathological reports to improve the accuracy of diagnosis and management of breast disease. J Dhaka Med Coll. 2022; 31(1) : 107-113